An evaluation on the effectiveness, development and establishment of the pharmacist-assisted heart failure management tools - Gopal, Cynthia Priyadarshini (2016)
Underutilization of pharmacotherapy is one of the major factors limiting morbidity and mortality benefits among heart failure (HF) patients. Pharmacistassisted HF management has proven beneficial in developed countries though such data is lacking in Malaysia. This single centre study was designed to evaluate the development, establishment and effectiveness of pharmacist-assisted heart failure management tools (PAHMT) on optimizing HF therapy, improving morbidity and mortality, and humanistic outcomes (knowledge, self-care, quality of life, illness perception, medication adherence and patient satisfaction). This study was divided into 3 components.